PENGGUNAAN APLIKASI MOBILE LEARNING BERBASIS HTML 5 UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA MATA KULIAH MIKROBIOLOGI - Hernawan, Hudiana (Universitas Pendidikan Indonesia, 2017)
This research was based on the phenomenon that the learning that has been done was not optimal to raise the understanding in studying the microbiology subject, it is indicated by the numbers of the students who have not been able to reach the expected learning result. It showed that the learning process of Microbiology subject needs to be developed with different approach, that is by using the application of mobile learning based HTML5 . The aim of this research is to figure out: the use of mobile learning based HTML5 in improving students understanding in Microbiology course. The result of this research can be concluded that the average of pretest and posttest score in experiment class was 54,77 and 79,96 with normalized gain value is 0.56 (medium category). While in the control class the average pretest and posttest score was 39.96 and 61.19 with normalized gain value is 0.35 (medium category). There was different average score on posttest and increase understanding of students who used mobile learning based HTML5 application on real higher than the students who studied in conventional learning method.